FAUST: an environment for programming parallel scientific applications - Guarna, V. A.; Gannon, D.; Gaur, Y.; Jablonowski, D. (Proceedings of the 1988 ACM/IEEE conference on Supercomputing, 1988)
The subject of integrated programming environments for scientific computing has become very popular over the last few years. Environments such as Rn [3] are being constructed to help coordinate the disjoint activities of editing, debugging, and performance tuning typically seen in the development cycle for software for complex parallel architectures [13]. This paper overviews the Faust project at the Center for Supercomputing Research and Development at the University of Illinois. Faust is targeted at providing an integrated setting for the development of scientific applications. The overall structure of the Faust environment is presented, along with a discussion of some specific tools used to aid the applications programmer in the development of codes.